What Drives the Rapid Economic Growth in Azerbaijan? - An Application of the Solow Model - Shaokai Huang (European Scientific Journal, ESJ, 2016)
Azerbaijan has undergone significant economic transformation and development since the country’s independence in 1991. Azerbaijan has quickly transformed itself into an upper middle income country. The rapid economic development is mainly attributed to the exploitation of hydrocarbon resources (through production sharing agreements with foreign oil companies and foreign direct investment). Substantial reforms intended to support a market-based economy have been instrumental in facilitating economic growth. This paper applies the Slow Model to explain factors that drive the rapid economic growth in Azerbaijan. This paper discusses the theoretical role of capital, labor, and technology in economic growth and illustrates the impact of corresponding factors in practice, i.e., foreign investment, labor force, education, and technology, on Azerbaijan’s economic growth.